Correlation between Serum Ferritin, Serum Cystatin C, and Renal Function in Children with β Thalassemia Major - Permadi, Suci Saptyuni; Renarti, Lelani; Rachmadi, Dedi (Faculty of Medicine, Universitas Padjadjaran, 2019)
Renal dysfunction caused by iron overload is characterized by an increase in ferritin and cystatin C levels. The objective of this study was to determine the correlation between ferritin, cystatin C, and renal function in children with β thalassemia major. A cross-sectional observational analytic study was conducted in September 2018 on 34 children with β thalassemia major in Dr. Hasan Sadikin General Hospital. Ferritin and cystatin C levels were documented and the estimated glomerular filtration rate (eGFR) was calculated using the Schwartz formula. Statistical tests were performed using Rank Spearman and Point Biserial with p value of <0.05 considered significant. the median ferritin level, cystatin C level, and eGFR of the subjects were 2,818 ng/mL (95% CI: 2,505–3,977), 209.9±121.5 (95% CI: 167.5–252.3), and 185.5 mL/min /1.73 m2 (95% CI: 173.6–208.2), respectively. Correlations were sought between serum ferritin and eGFR (r=0.132, p=0.229), between cystatin C and eGFR: r=0.3012, p=0.041, and between ferritin and cystatin C: r=0.433, p=0.011. No correlation was found between ferritin and renal function whereas serum cystatin C presented a positive correlation with renal function. A strong correlation was found between ferritin and cystatin C. Serum ferritin and cystatin C are promising biomarkers to assist in monitoring renal function in children with β thalasemia major.Hubungan Feritin dan Cystatin C Serum dengan Fungsi Ginjal pada Anak Talasemia β Mayor Kelebihan besi pada anak talasemia β mayor mengganggu organ vital di antaranya ginjal. Gangguan fungsi ginjal karena kelebihan besi dapat ditandai dengan peningkatan kadar ferritin dan cystatin C. Penelitian ini bertujuan mengetahui hubungan kadar feritin dan cystatin C dengan fungsi ginjal pada anak talasemia β mayor. Penelitian observasional analitik dengan rancangan potong lintang, dilaksanakan bulan September 2018. Subjek penelitian adalah anak penderita talasemia β mayor di Rumah Sakit Dr. Hasan Sadikin Bandung. Dilakukan pemeriksaaan kadar feritin dan cystatin C. Penilaian fungsi ginjal menggunakan estimated glomerular filtration rate (eGFR) dengan formula Schwartz. Uji statistik menggunakan uji Rank Spearman dan Point Biserial dengan kemaknaan berdasar nilai p<0,05. Didapatkan jumlah sampel sebanyak 34 anak, dengan kadar feritin median 2818 ng/mL (IK95%:2505–3977), cystatin C 209,9±121,5 (IK95%:167,5–252,3) dan eGFR median 185,5 mL/menit per 1,73 m2(IK95%:173,6–208,2). Korelasi antara kadarferritin dengan eGFR: r=0,132, p=0,229, korelasi cystatin C dengan eGFR: r=0,3012; p=0,041 dan korelasi kadar feritin dengan cystatin C: r=0,433; p=0,011). Hasil penelitian ini tidak didapatkan korelasi antara feritin dan fungsi ginjal, sedangkan cystatin C memiliki korelasi positif dengan fungsi ginjal. Didapatkan korelasi kuat antara kadar feritin dan cystatin C serum. Pemeriksan kadar feritin dan cystatin C dapat membantu pemantauan fungsi ginjal pada anak talasemia β mayor.